2007
DOI: 10.1002/ceat.200600407
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Linalyl Acetate from Linalool in Supercritical Carbon Dioxide: A Thermodynamic Study

Abstract: The main components of Lavender and Lavandin essential oils are linalyl acetate and linalool. An enrichment of the product in linalyl acetate is of interest, since the market value of this component is considerably higher than that of linalool. This work presents a thermodynamic study of the synthesis of linalyl acetate from linalool by a catalytic transesterification with ethyl acetate in a supercritical CO 2 medium. The study comprises the calculation of the equilibrium compositions of this reaction, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…The product was further purified on a column chromatograph to give linalyl acetate in 98.1% purity as a liquid. The identity of linalyl acetate was confirmed by 1 H and 13 C NMR spectral data …”
Section: Methodsmentioning
confidence: 81%
“…The product was further purified on a column chromatograph to give linalyl acetate in 98.1% purity as a liquid. The identity of linalyl acetate was confirmed by 1 H and 13 C NMR spectral data …”
Section: Methodsmentioning
confidence: 81%
“…Linalyl acetate increasing by rise of temperature may probably be due to the formation of new byproducts from the volatility of others (linalool) (Dorneles et al, 2019). Furthermore, it can be hypothesized that linalool conversion to linalyl acetate is one of the chemical transformations of essential oil compounds by increasing drying temperature (Martín et al, 2007). Srinivas et al (2020) observed lower myristicin, oleoresin, and volatile oil percentage of M. fragrans during drying process by sun and convective drying compared with the microwave assisted fluidized bed.…”
Section: F I G U R Ementioning
confidence: 99%
“…Linalool is a key building block for the synthesis of various vitamins and fragrances, in particular, linalyl acetate, which is extensively used in food applications, differently from linalool itself. 5 Nerolidol is also available from essential oils of various plants and owers, which may contain up to 50-90% of this sesquiterpenoid with a delicate sweet oral and woody odor. The use of nerolidol can be signicantly extended by its esterication.…”
Section: Resultsmentioning
confidence: 99%
“…These monoterpenic alcohols are commonly used in non-food applications, whereas linalyl acetate and geranyl acetate are particularly appreciated as food additives due to low toxicity, high stability and special avors. 5,6 Terpenic acetates can be produced by acid-catalyzed esteri-cation of alcohols with acetic acid, alkyl acetates or acetic anhydride. 4 A number of acidic catalysts, such as CoCl 2 , 7 zeolites, 8 trimethylsilyl triuoromethanesulfonate, 9 Ce(OTf) 3 (ref.…”
Section: Introductionmentioning
confidence: 99%